MODEL ROLE PLAY SEBAGAI STRATEGI PEMBELAJARAN UNTUK MENINGKATKAN KESIAPSIAGAAN SISWA PADA LITERASI BENCANA - Aprilianti; Ahmad Mulyadiprana; Pidi Mohamad Setiadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
One of the things that students need to learn is environmental conditions, which are related to a disaster. Disasters are a series of events that can happen at any time and require a preparedness attitude. With events that can happen at any time, disaster preparedness is very important for all residents, especially among elementary school students who are vulnerable groups. This can be implemented through learning in elementary schools, one of which discusses environmental and social conditions. This study uses a qualitative method with data collection techniques through interviews, observations and literature studies. The findings of this study include: The use of role play learning models can be a strategy in increasing student preparedness for disaster literacy in elementary schools; Preparedness in facing disasters is very important to reduce the risk of disasters that can occur at any time. Through the role play approach, students not only understand the concept of disaster theoretically, but can also be done in real situations in emergency situations through role play simulations.